2014
DOI: 10.1002/2013jd021208
|View full text |Cite
|
Sign up to set email alerts
|

On the distribution of CO2 and CO in the mesosphere and lower thermosphere

Abstract: We have used the Whole Atmosphere Community Climate Model (WACCM) to calculate the distribution of CO 2 and CO in the mesosphere and lower thermosphere (MLT), and we have compared the results with observations, mainly from the Atmospheric Chemistry Experiment Fourier Transform Spectrometer and Michelson Interferometer for Passive Atmospheric Sounding satellite-borne instruments. We find that WACCM can reproduce the observed distribution of CO 2 in the MLT and the rapid falloff of CO 2 above about 80 km. Analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
182
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 117 publications
(209 citation statements)
references
References 54 publications
18
182
0
Order By: Relevance
“…This can be explained by diffusive separation, which becomes pronounced in the upper mesosphere because SF 6 is a relatively heavy molecule (molar mass 0.146 kg) compared to the mean mass of air molecules (mean molar mass 0.0288 kg; cf. Garcia et al 2014, where similar behaviour is seen for CO 2 , another relatively heavy molecule). Panels a-c of the figure all show SF 6 decreasing above ∼ 80 km, and panels a and c are almost identical, while in panel b the decrease begins about 4 km lower.…”
Section: Infrared Absorption Spectrum and Radiative Forcingsupporting
confidence: 60%
See 1 more Smart Citation
“…This can be explained by diffusive separation, which becomes pronounced in the upper mesosphere because SF 6 is a relatively heavy molecule (molar mass 0.146 kg) compared to the mean mass of air molecules (mean molar mass 0.0288 kg; cf. Garcia et al 2014, where similar behaviour is seen for CO 2 , another relatively heavy molecule). Panels a-c of the figure all show SF 6 decreasing above ∼ 80 km, and panels a and c are almost identical, while in panel b the decrease begins about 4 km lower.…”
Section: Infrared Absorption Spectrum and Radiative Forcingsupporting
confidence: 60%
“…The model contains a detailed treatment of middle atmosphere chemistry including interactive treatments of Na and K . We use the specified dynamics (SD) version of the model to allow comparison with observations (see Garcia et al, 2014, for details). The SF 6 surface emission flux and initial global vertical profiles were taken from a CCMI (Chemistry Climate Model Initiative) simulation using the same version of SD-WACCM with the same nudging analyses (D. Kinnison, personal communication, 2013).…”
Section: Photolysismentioning
confidence: 99%
“…Lastly, (3) these discrepancies might be related to the WACCM representation of the mean meridional circulation which has been shown to have some deficiencies (Smith et al, 2011;Smith, 2012), suggesting that the gravity wave parametrization needs to be modified. In addition, Garcia et al (2014) have shown that adjusting the Prandtl number, used to calculate the diffusivity due to gravity waves, significantly alters the CO 2 SD-WACCM simulations, improving the agreement with satellite measurements. Such adjustment should also affect the H 2 O and hence the HO x chemistry.…”
Section: Comparison With a Global Climate Modelmentioning
confidence: 99%
“…This vertical branch of the meridional circulation can transport gases with high thermospheric volume mixing ratios (VMRs), and change the composition of the middle atmosphere (e.g. Solomon et al, 1985;Allen et al, 2000;Hauchecorne et al, 2007;Smith et al, 2011;Garcia et al, 2014;Manney et al, 2009;2015;Funke et al, 2014aFunke et al, , b, 2017. The downward transport of nitrogen oxide (NO), produced at around 110 km through energetic particle precipitation (EPP) events (e.g.…”
Section: Introductionmentioning
confidence: 99%